Investigation on the Effect of the Shaft Transition Form on the Inflow Pattern and Hydrodynamic Characteristics of the Pre-Shaft Tubular Pump Device - Luo, Can; Du, Kang; Qi, Weijun; Cheng, Li; Huang, Xianbei; Lu, Jiaxing (Frontiers in Energy Research, 2022)
The shaft tubular pump device is widely used in low head pumping stations in plain areas. Investigation based on the N-S equation and the SST k-ω turbulence model are carried out to investigate the effect of the shaft transition form on the inflow pattern and hydrodynamic characteristics of pre-shaft tubular pump device, and the optimal transition case is verified experimentally. Three types of transition shafts are designed to provide different inlet conditions for the tubular pump device, and the characteristic section parameters of the shafts, external and internal flow characteristics of the pumping device under different inlet conditions are compared and analyzed, and the optimal transition form is selected for model tests and non-constant pressure pulsation characteristics are studied. The results show that the flow pattern in the inlet passage of each case is relatively uniform and smooth, and the range of the high efficiency zone of the pump device is roughly within 0.9Qd - 1.2Qd. The energy loss and the weighted average angle of the outlet section are similar under each case, and the uniformity of the axial velocity distribution in the inlet section of the impeller of case 1 is better than the other cases. The numerical simulation results are consistent with the experimental results, and the numerical simulation method is reliable. Under the design flow condition, the pressure pulsation amplitude at the impeller inlet is the largest, showing the trend of gradually increasing from the hub to the rim, and the main frequency of pressure pulsation is the leaf frequency, while the pressure pulsation amplitude at the impeller outlet shows the trend of large in the middle and small on both sides from the hub to the rim, and the rim is obviously influenced by the static and dynamic interference, and the main frequency is changed. The research results can provide reference for the design and optimization of shaft tubular pump device, which has certain theoretical and engineering value.